2022
DOI: 10.1177/13558196221091356
|View full text |Cite
|
Sign up to set email alerts
|

Processes supporting effective skill-mix implementation in general practice: A qualitative study

Abstract: Objectives Health policy and funding initiatives have addressed increasing workloads in general practice through the deployment of clinicians from different disciplinary backgrounds. This study examines how general practices in England operate with increasingly diverse groups of practitioners. Methods Five general practices were selected for maximum variation of the duration and diversity of skill-mix in their workforce. Individual interviews were recorded with management and administrative staff and different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…As far as we are aware, our study is the first to include views on MDT working as part of the new GP contract in Scotland and our findings raise questions, not only about the numbers of staff being recruited, but also how effectively new staff are being integrated and embedded into primary care teams and the culture of general practice. Recent research in England has identified the complexity of matching' patients' needs with practitioners' capabilities when trying to reduce GP workload by redistributing workload to MDTs [18]. A recent King's Fund report on the expansion of MDT staff in Primary Care Networks (PCNs) in England also concluded that "while PCNs have swiftly recruited to these roles, they are not being implemented and integrated into primary care teams effectively" [19, p. 2].…”
Section: Relationship With Published Literaturementioning
confidence: 99%
“…As far as we are aware, our study is the first to include views on MDT working as part of the new GP contract in Scotland and our findings raise questions, not only about the numbers of staff being recruited, but also how effectively new staff are being integrated and embedded into primary care teams and the culture of general practice. Recent research in England has identified the complexity of matching' patients' needs with practitioners' capabilities when trying to reduce GP workload by redistributing workload to MDTs [18]. A recent King's Fund report on the expansion of MDT staff in Primary Care Networks (PCNs) in England also concluded that "while PCNs have swiftly recruited to these roles, they are not being implemented and integrated into primary care teams effectively" [19, p. 2].…”
Section: Relationship With Published Literaturementioning
confidence: 99%
“…These studies were conducted during a period of relative stability before the COVID-19 pandemic whereas our study may have been affected by restrictions imposed during the pandemic, despite our primary end point being in the post-pandemic recovery period. Additionally, the transfer of tasks from GPs to non-GP practitioners was identified as a key challenge to be faced by the newly formed PCNs (32). Our outcome was three years after PCNs were introduced, which may have given PCNs sufficient time to address this challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Policy led changes to skill mix often assume that work can be broken down into discrete, stable tasks. However, research suggests that this provides an impoverished vision of what good quality care looks like, especially in contexts such as general practice 11. Historic workforce forecasting has been based on the number of people in training and education, with much less attention paid to retaining existing staff throughout the career lifecycle.…”
Section: Changing State Of Knowledgementioning
confidence: 99%